Identifikasi penyebab infeksi STH (soil transmitted helminth) di Panti Sosial Tresna Werdha Sinta Rangkang, Kota Palangka Raya - Elfatia, Nurwafa; Toemon, Agnes Immanuella; Ratnasari, Arini; Augustina, Indria; Faradila (Tropis: Jurnal Riset Teknologi Laboratorium Medis, 2024)
Helminth infection is a health problem that is included in countries with tropical and sub-tropical climates. Helminth infection do not always attack the age group of schoolchildren but can also attack the elderly group, STH worms (Soil-transmitted helminths) are worms transmitted through the soil and feces of infected people, types of STH worms namely Ascaris lumbricoides (roundworms), Trichuris trichiura (whipworms), and Ancylostoma duodenale, Necator americanus (hookworm). This study aims to determine the identification of the cause of the infection of STH (Soil Transmitted Helminth) inthe Tresna Werdha Sinta Rangkang Tangkiling Social Institution. This study approach used 34 respondents, which was obtained by purposive sampling technique. From the results of fecal research conducted by the elderly, no worms were found. Stool samples were studied using the kato katz method. It can be concluded that there are no elderly helminth infection at the Tresna Werdha Sinta Rangkang Tangkiling Social Institution.